PENGARUH PANDEMI COVID-19 TERHADAP BUDAYA BOTRAM DAN MAKAN LALAPAN PADA MAHASISWA ITB SUKU SUNDA ASAL DAERAH TASIKMALAYA, JAWA BARAT - Muhammad Fairuziko Nurrajab; M. Alvin Syukriant; Rumaisa Hilwa Maulida (Universitas Warmadewa, 2021)
The COVID-19 pandemic has affected the majority of sectors in Indonesia. One of them is in the cultural sector, especially the culture of the Sundanese community regarding botram culture and eating lalapan. This research was conducted to determine the effect of the COVID-19 pandemic on botram culture and fresh vegetables in the Sundanese people living in the Tasikmalaya area. The target of this research is ITB students who live in the Tasikmalaya area and are Sundanese people. This research was conducted using research methods through literature studies and online surveys. The results of this study indicate that there is a significant decrease in the amount of botram during the pandemic. Meanwhile, the culture of lalapan does not have a significant change, so it can be concluded that the pandemic has not affected the habits of the Sundanese people in consuming lalapan. Keywords: the COVID-19 pandemic; botram; eating lalapan; Sundanese society; Tasikmalaya